4-Nonylphenol reduces cell viability and induces apoptosis and ER-stress in a human epithelial intestinal cell line. Issue 7 (October 2015) - Lepretti, M.; Paolella, G.; Giordano, D.; Marabotti, A.; Gay, F.; Capaldo, A.; Esposito, C.; Caputo, I.
Highlights The surfactant 4-nonylphenol (4-NP) is a common food contaminant. 4-NP is cytotoxic for undifferentiated human intestinal Caco-2 cells. 4-NP displays anti-proliferative effects and interferes with EGF signalling. 4-NP induces cell apoptosis and triggers an ER-stress response. A daily intake of 4-NP-containing food may have harmful effects on human intestine.